(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Due to a lengthy and omissive Legislative Power, the protection against arbitrary or unfair dismissal, provided in item 7 of article 7, of the Brazilian Federal Constitution of 1988, remains a promise of arduous fulfillment. This is because, after more than thirty years of the promulgation of the Magna Carta, no serious legislative movement is envisaged to edit the complementary law mentioned in the constitutional text, which would protect the employee from the arbitrariness of the employer’s resilient power. In this context, the objective of this study is to analyze if the link between the exercise of the referred right to the edition of another norm would be the result of the maneuver of underlying social phenomena, with the purpose of not realizing the right, in the mold of the so-called “Symbolic Constitutionalization”. To this end, it is necessary to elucidate the influence of ideology on law in order to unravel the occurrence of political pressure on the part of certain social groups, and how legislative production can serve as an instrument for the attainment of particular aspirations of these segments through ideological apparatus of the state itself. Using the deductive method and bibliographic research, this article concludes that the constituent state, through its legal ideological apparatus, included in the constitution a normative text marked by symbolic hypertrophy, in order to contain the expectations of the working class regarding protection against arbitrary dismissal or without just cause, but without the real intention of giving it effect.